2007
DOI: 10.1556/abiol.58.2007.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic innervation of the pancreas in the sheep

Abstract: Antibodies raised against vesicular acetylcholine transporter (VAChT) were applied to study the cholinergic innervation pattern of the pancreas of the sheep. To determine whether the cholinergic pancreatic neuronal elements contain tyrosine hydroxylase (TH), neuropeptide Y (NPY), vasoactive intestinal peptide (VIP) or substance P (SP) double immunocytochemistry was used. A moderate number of VAChT-immunoreactive (IR) nerve terminals were distributed between the acini, whereas only single cholinergic nerve fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
6
0
4
Order By: Relevance
“…Taking into account the above findings, it is suggested that in sheep NO may mainly stimulate glucagon production evoked by cholinergic muscarinic transmission whereas inhibition of insulin secretion may be of minor importance. Such assumption is based on the following: in the present study we indicated the possibility of intrinsic nitrergic supply to pancreatic islets, virtually all intrapancreatic neurones were shown to express VAChT (Arciszewski and Zacharko‐Siembida, 2007a) and within islets the vast majority of nNOS‐IR nerve terminals surrounded endocrine cells of external layers (as mentioned above most likely to be α ‐cells).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Taking into account the above findings, it is suggested that in sheep NO may mainly stimulate glucagon production evoked by cholinergic muscarinic transmission whereas inhibition of insulin secretion may be of minor importance. Such assumption is based on the following: in the present study we indicated the possibility of intrinsic nitrergic supply to pancreatic islets, virtually all intrapancreatic neurones were shown to express VAChT (Arciszewski and Zacharko‐Siembida, 2007a) and within islets the vast majority of nNOS‐IR nerve terminals surrounded endocrine cells of external layers (as mentioned above most likely to be α ‐cells).…”
Section: Discussionsupporting
confidence: 54%
“…However, the presence of choline acetyltransferase in the guinea‐pig nitrergic intrapancreatic neurones has led to substantial revision of this concept and the possible role of NO in co‐transmission has been suggested (Liu et al., 1998). Of note, all neurones of the ovine pancreas were shown to express the vesicular acetylcholine transporte (VAChT; Arciszewski and Zacharko‐Siembida, 2007a), which means that NO may co‐exist with acetylcholine and that nitrergic neurones, presumably acting as interneurones, may be involved in modulation or co‐transmission of responses to cholinergic nerve stimulation. However, the total view is additionally complicated by the finding that nNOS‐positive neurones also co‐store VIP and NPY.…”
Section: Discussionmentioning
confidence: 99%
“…VAChT and TH were shown to be colocalized in distinct populations of nerve fibers among the acini. TH was present in the vast majority of VAChT-positive intrapancreatic perikarya [14]. Studies of adrenergic pancreatic innervation in sheep revealed that most DbH-positive nerve fibers occur in the parenchyma between the acini, around blood vessels, and in the connective tissue, but only a small amount of adrenergic intrapancreatic neurons were found.…”
Section: Discussionmentioning
confidence: 95%
“…Autonomic innervation of the pancreas has been investigated in numerous vertebrate species, both in domestic animals, such as pigeon [9,10], hen [11], cat [12], rabbit [12,13], sheep [14,15], pig [16], and the representatives of other species, such as the African silverbill [9,10], and mainly rodents, such as rat [12,17], mouse [5,6,18], or Egyptian spiny mouse [19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that choline acetyltransferase (CHAT)-immunopositive neuronal cell bodies and nerve fibers are present in the pancreas of many species (Liu et al, 1998; Love and Szebeni, 1999a; Wang et al, 1999), suggesting that ACh is not only released from parasympathetic efferents and enteropancreatic fibers, but also from the neurons in the intrapancreatic ganglia. However, intrapancreatic ganglia are not innervated by cholinergic nerve fibers in the sheep pancreas (Arciszewski and Zacharko-Siembida, 2007), which suggests that the cholinergic innervation of islets from pancreatic neurons is species-dependent.…”
Section: Neurotransmitters Of Intrapancreatic Gangliamentioning
confidence: 99%